The effects of microbial fertilizer based Aspergillus brunneoviolaceus HZ23 on pakchoi growth, soil properties, rhizosphere bacterial community structure, and metabolites in newly reclaimed land - Li, Xuqing; Li, Dingyi; Jiang, Yugen; Xu, Jun; Ren, Xiaoxu; Zhang, Ya; Wang, Hong; Lu, Qiujun; Yan, Jianli; Ahmed, Temoor; Li, Bin; Guo, Kai (Frontiers in Microbiology, 2023)
Pakchoi is an important leafy vegetable in China. Due to industrialization and urbanization, pakchoi has been cultivated in newly reclaimed mountainous lands in Zhejiang Province, China in recent years. However, immature soil is not suitable for plant growth and needs to be modified by the application of different organic fertilizer or microbial fertilizer based plant-growth-promoting microbe. In 2021, a high efficient plant-growth-promoting fungi (PGPF)(Aspergillus brunneoviolaceus HZ23) was obtained from newly reclaimed land of Zhejiang Province, China. In order to evaluatemicrobial fertilizer basedA. brunneoviolaceus HZ23 (MF-HZ23) on pakchoi growth in immature soil, we investigated the effect of MF-HZ23 on soil properties, rhizosphere bacterial community structure and metabolites of pakchoi rhizosphere soil samples. The results revealed a significant difference between MF-HZ23 and the control in soil properties,bacterial community structure and metabolites. Indeed, compared with the control, MF-HZ23 caused 30.66%, 71.43%, 47.31%, 135.84% and 2099.90% increase in the soil pH, organic matter contents (OMC), total nitrogen (N), alkaline hydrolysis nitrogen (AHN) and available phosphorus (P), respectively. Meanwhile, MF-HZ23 caused 50.78%, 317.47%, 34.40% increase in the relative abundance of Proteobacteria, Bacteroidota, Verrucomicrobiota and75.55%, 23.27%, 69.25%, 45.88%, 53.42%, 72.44% reduction inthe relative abundance ofAcidobacteriota, Actinobacteriota, Chloroflexi, Planctomycetota, Patescibacteria, WPS-2, respectively, compared with the control based on 16S amplicon sequencing of soil bacteria. Furthermore, redundancy discriminant analysis (RDA) of bacterial communities and soil properties indicated that the main variables of bacterial communities included available P, AHN, pH, OMC and total N. In addition, non-targeted metabolomics techniques (UHPLC-MS analysis) revealed that there were six differentially expressed matabolites (DEMs) belong to organoheterocyclic compounds, organic acids and derivatives, organic nitrogen compoundsinMF-HZ23 and the control group, and these six DEMs were significantly positively correlated with 23 genus of bacteria, which showed complicated interactions between bacteria and DEMs in pakchoi rhizosphere soil. Overall, the results of this study revealed significant modification in physical, chemical and biological properties of pakchoi soil. Microbial fertilizer based PGPF A. brunneoviolaceus HZ23 (MF-HZ23) can be used as a good amendment for newly reclaimed land.